Analysis of financial ratios as determinants of stock price changes - Alisa Amelia; Muhammad Ansar; Ni Made Suwitri Parwati; Ernawaty Usman (Institute of Accounting Research and Novation (IARN), 2026)
Focusing on banking companies listed on the IDX from 2021 to 2025, this study aims to analyze the impact of the LDR, NPL, NIM, and CAR on their stock prices. A panel data regression model and a quantitative methodology are used in this investigation. 41 businesses that satisfied the requirements during the study period were chosen using the purposive sample technique; as a result, the dataset had 205 data points. The findings show that whereas CAR significantly and favorably affects stock prices, LDR, NPL, and NIM have no influence. The variables examined in this study were restricted to LDR, NPL, NIM, and CAR, and cannot yet be applied to the whole banking sector, among other constraints. In order to present a more complete picture, future study is urged to incorporate more factors and prolong the observation duration.